2001
DOI: 10.1038/oby.2001.62
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Young Women to Recall Past Body Size and Age at Menarche

Abstract: KOPROWSKI, CAROL, RALPH J. COATES, AND LESLIE BERNSTEIN. Ability of young women to recall past body size and age at menarche. Obes Res. 2001;9: 478 -485. Objective: The ability of young women (n ϭ 132, average age 17 years) to recall body size and age at menarche was examined. The use of body silhouettes to assist women in recalling their body size at menarche and to represent their current body size was also evaluated. Research Methods and Procedures: Subjects, who previously participated in a cohort study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 19 publications
5
88
1
Order By: Relevance
“…The test-retest method yielded high reliability (Kappa ¼ 0.81) in a report from Italy (Bosetti et al, 2001), and in Sweden, Bergsten-Brucefors (1976) found correlations between actual age at menarche and recall after 4 years to be high. The same results were found in the U.S. (r ¼ 0.83; Koprowski et al, 2001). In summary, this work reports the first estimate of age at menarche in Caboclo populations as well as an evaluation of the secular changes that have occurred in this physiological variable over a 50-year span.…”
Section: Discussionsupporting
confidence: 66%
“…The test-retest method yielded high reliability (Kappa ¼ 0.81) in a report from Italy (Bosetti et al, 2001), and in Sweden, Bergsten-Brucefors (1976) found correlations between actual age at menarche and recall after 4 years to be high. The same results were found in the U.S. (r ¼ 0.83; Koprowski et al, 2001). In summary, this work reports the first estimate of age at menarche in Caboclo populations as well as an evaluation of the secular changes that have occurred in this physiological variable over a 50-year span.…”
Section: Discussionsupporting
confidence: 66%
“…In the present study, the mean interval of recall was 2.5 years, and 63% of the adolescents had reached menarche within three years of the time of interview. Previous studies that used a similar recall procedure reported a correlation coefficient of 0.83 and 0.67 between the actual and the recalled age at menarche when the mean interval of recall compared to occurrence of menarche was 4.8 years and 33 years respectively (18,19). Therefore, the recall errors are expected to be low in this study due to the relatively short interval of recall.…”
Section: Discussionmentioning
confidence: 84%
“…43 The most important limitation of the current study may be our use of self-reported menarcheal age. Correlations between recalled and recorded menarcheal ages have generally been high (r Ͼ 0.75) over periods of up to 10 years, 44,45 with 60% of girls being able to recall the month and year of menarche over short periods. 46 Additional analyses (data not shown) of 1082 girls in Bogalusa who were examined 2 times after menarche suggested that the reproducibility of menarcheal age in the current study was somewhat lower (r ϭ 0.57), possibly as a result of our lack of information on month of menarche.…”
Section: Discussionmentioning
confidence: 99%